Efectividad del protocolo SMILE lite para la estimación del color dental en resinas - Luis Eduardo, Chávez Paredes (2021)
In Dentistry field, the most common colour estimation method is the visual method. Thus, many professionals have difficulty in choosing tooth colour. This is extremely important in order to provide patients with successful aesthetic treatments. This research evaluates the effectiveness of the Smile Lite Protocol for colour estimation in three Nano-hybrid resins usually used in dental restorations. This is an In Vitro and Observational study in 45 resin discs wholly, 15 Tetric N Ceram discs, 15 Grandio resin discs and 15 Filtek Z350 resin discs were used. The effectiveness of the Smile Lite Protocol was good in terms of shade, but some adjustments are still needed in terms of saturation since the agreement is poor and even compared to the VITA Classic colorimeter. The effectiveness of the Smile Lite Protocol according to the Kappa match index was 0.26 (Weak match) when referring to the factory colour for saturation; meanwhile for hue, the match was accurate (High match). Even when comparing between the other colour estimation method the effectiveness of the Smile Lite Protocol according to the Kappa match index was 0.19 (Poor match) with respect to the Vita Classic colorimeter.